Public perceptions of private security in shopping malls: A comparison of the United Kingdom and South Korea - Kim, Hyunho (International journal of law, crime and justice, 2018)
This paper provides one of the first comparative empirical studies of private policing in equivalent shopping malls in the UK and Korea. The paper is based upon 200 interviews with customers who visited the malls, 200h observation and 39 interviews with security officers and other stakeholders. The paper builds upon the traditional orientations of security officers as either ‘watchmen' or ‘parapolice' to offer a third ‘servicemen' orientation. The paper also illustrates a variety of other differences in roles and shows the generally positive views of the public towards private security.